ESG disclosure, capital structure, and profitability in explaining firm value of Indonesia’s IDX ESG Leaders: Some notes from Islamic finance perspectives‎ - Dewi, Hastin Riska; Muhyarsyah, Muhyarsyah (Universitas Islam Indonesia, 2026)
IntroductionThe increasing importance of sustainability and responsible investment has led to growing attention to environmental, social, and governance disclosure in global markets. In Indonesia, the establishment of the IDX ESG Leaders index provides a relevant platform to evaluate how such disclosure, alongside financial fundamentals, contributes to firm value. Despite expectations that non-financial transparency enhances valuation, empirical findings in emerging markets remain inconsistent, warranting further investigation.ObjectivesThis study examines the effects of environmental, social, and governance disclosure and capital structure on firm value among firms listed in the IDX ESG Leaders index from 2020 to 2023. It also explores whether profitability moderates these relationships by strengthening or weakening their impact on valuation.MethodThe research adopts a quantitative approach using panel data regression with 68 firm-year observations from 17 IDX ESG Leaders firms. ESG disclosure indices were constructed through content analysis of annual and sustainability reports, while financial data were obtained from audited statements. Profitability, proxied by return on assets, was incorporated as a moderating variable through moderated regression analysis to identify conditional effects.ResultsThe findings reveal that environmental and social disclosure do not directly influence firm value, while governance disclosure exerts a significant negative effect. Capital structure shows a strong positive impact, and profitability both directly enhances firm value and moderates certain relationships. Specifically, profitability weakens the effect of social disclosure but strengthens the influence of capital structure, suggesting that investors prioritize financial fundamentals over non-financial reporting.ImplicationsThe results highlight the conditional relevance of ESG disclosure in emerging markets and reinforce the continuing importance of profitability and capital structure. Theoretically, the study challenges the universality of stakeholder and signaling theories by revealing context-dependent effects. Practically, it provides guidance for managers to align disclosure with financial strength and for policymakers to strengthen ESG reporting standards.Originality/NoveltyThis study contributes to the literature by disaggregating ESG disclosure into environmental, social, and governance dimensions and incorporating profitability as a moderating variable. It provides new evidence from Indonesia’s capital market, offering insights into how non-financial transparency interacts with financial strategies to shape firm value.